2019
DOI: 10.3847/1538-4365/ab3662
|View full text |Cite
|
Sign up to set email alerts
|

Bright Southern Variable Stars in the bRing Survey

Abstract: In addition to monitoring the bright star β Pic during the near-transit event for its giant exoplanet, the β Pictoris b Ring (bRing) observatories at Siding Springs Observatory, Australia and Sutherland, South Africa have monitored the brightnesses of bright stars (V;4-8 mag) centered on the south celestial pole (δ−30°) for approximately two years. Here we present a comprehensive study of the bRing time-series photometry for bright southern stars monitored between 2017 June and 2019 January. Of the 16,762 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(112 reference statements)
0
4
0
Order By: Relevance
“…• HD 156623: based on observations with the bRing robotic observatory network, Mellon et al 91 found frequencies in the range 60-70 d −1 and suggested regularity at three different separations: 3.75, 7.25, and 2.75d −1 . This star was observed by TESS in sector 12 and shows a pattern similar to other stars in our sample, with a spacing of ∆ν = 7.31 d −1 .…”
Section: Additional References and Notesmentioning
confidence: 99%
“…• HD 156623: based on observations with the bRing robotic observatory network, Mellon et al 91 found frequencies in the range 60-70 d −1 and suggested regularity at three different separations: 3.75, 7.25, and 2.75d −1 . This star was observed by TESS in sector 12 and shows a pattern similar to other stars in our sample, with a spacing of ∆ν = 7.31 d −1 .…”
Section: Additional References and Notesmentioning
confidence: 99%
“…This allows the combination of data between the two bRing stations and the southern MASCARA station. Further discussion on the systematic errors encountered by the bRing stations can be found in Mellon et al (2019c).…”
Section: Mascara Bring and Discovery Observationsmentioning
confidence: 99%
“…The MASCARA survey utilises two stations, located in the northern and southern hemisphere, to search for transiting exoplanets. For this purpose, it obtains continuous, high-cadence observations of the brightest stars in the sky (4 < V < 8.4), and such observations are also very well-suited for use in variable star studies (Mellon et al 2019). HD 27130 passes over the east, west and zenith pointing cameras of the northern MASCARA station and we use data obtained between February 2015 and August 2018.…”
Section: Photometric Observations With Mascaramentioning
confidence: 99%